Relationship of Social Interactions to Learning Outcomes English - Ifna Nifriza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the relationship between social interaction and students' English learning outcomes. This study uses the correlation method. The population in this study amounted to 204 people. The sample is 32 people. Sampling was taken by random cluster sampling. The results showed that the average value of students' social interaction was 64, with sufficient qualifications. The average result of learning English is 79 with suitable qualifications. Therefore, there is a good relationship between student social interaction and Indonesian students' learning outcomes at SMA N 1 Akabiluru District. The test results prove that thitung>t table (3,268>1,697). In conclusion, there is a significant relationship between social interaction and the English learning outcomes of students at SMA N 1 Akabiluru District. Keywords: Learning Outcomes, Relationship, Social Interaction